Team Cooperation in a Network of Multi-Vehicle Unmanned Systems Synthesis of Consensus Algorithms - Semsar-Kazerooni, Elham. (Springer New York : Imprint: Springer, 2013)
Team Cooperation in a Network of Multi-Vehicle Unmanned Systems develops a framework for modeling and control of a network of multi-agent unmanned systems in a cooperative manner and with consideration of non-ideal and practical considerations. The main focus of this book is the development of synthesis-based algorithms rather than on conventional analysis-based approaches to the team cooperation, specifically the team consensus problems. The authors provide a set of modified design-based consensus algorithms whose optimality is verified through introduction of performance indices. This book also: Provides synthesis-based methodology for team cooperation Introduces a consensus-protocol optimized performance index Offers comparisons for use of proper indices in measuring team performance Analyzes and predicts performance of previously designed consensus algorithms Analyses and predicts team behavior in the presence of non-ideal considerations such as actuator anomalies and faults as well as the evolutions in the structure of the information exchange Team Cooperation in a Network of Multi-Vehicle Unmanned Systems is an ideal book for researchers as well as graduate-level university students who desire to work in the area of networked unmanned systems.